Polymer-supported catalysts for oxygen reduction and methanol oxidation - Shan, Jingning, 1970- (2000)
Thesis (M.Sc.)--Memorial University of Newfoundland, 2000. Chemistry Includes bibliographical references. This thesis is focused on the synthesis and characterization of poly(3,4-ethylenedioxythiophene)/poly(styrene-4-sulfonate) (PEDOT/PSS)-supported catalysts for the anodic oxidation of methanol as well as for cathodic oxygen reduction in low-temperature polymer electrolyte membrane fuel cells (PEFMCs). -- Chapter 2 focuses on the electrochemical and electrocatalytic properties of PEDOT/PSS supported Pt catalysts for cathodic oxygen reduction. Performances for oxygen reduction obtained in gas diffusion electrodes that are similar to those used in current PEMFC technology were inferior to those for commercial carbon supported Pt catalysts. Thus, the catalysts were immobilized on glassy carbon electrodes and were studied by cyclic voltammetry and rotating disc voltammetry. The results show that PEDOT/PSS supported Pt catalysts exhibit similar oxygen reduction activities to commercial carbon supported catalysts when results are normalized for active Pt area. Exchange current densities and mechanisms appear to be the same. The inferior performance seen for the PEDOT/PSS supported Pt catalysts in gas diffusion electrodes, and reproduced at rotating disc electrodes have been shown to be due to low Pt utilization, and to slightly higher Pt particle sizes. The poor utilization appears to be due to electronic isolation of some Pt particles, and to blocking or poisoning of the Pt surface. -- Chapters 3 and 4 focus on the preparation and characterization of PEDOT/PSS supported binary Pt-Ru, ternary Pt-Ru-OS and quaternary Pt-Ru-Os-Ir catalysts for anodic methanol oxidation. The compositions of the metal alloys can be controlled through the molar ratio of metal salts in the reaction mixture and by the reaction time. Energy-dispersive X-ray analysis and X-ray diffraction were applied to determine the metal compositions and particle sizes. The electrocatalytic properties of these catalysts were investigated by several electrochemical techniques, including cyclic voltammetry (including reduced C02 oxidation), transient and steady state polarization experiments and chronoamperometry. Although PEDOT/PSS supported binary catalysts have exhibited good electrocatalytic activities for methanol oxidation, their performances are inferior to commercial binary catalysts. PEDOT/PSS supported ternary and quaternary catalysts exhibited, as expected, superior performances to PEDOT/PSS supported binary catalysts, but are still inferior to those for commercial binary catalysts.